The effect of HIV prevention products on incentives to supply condomless commercial sex among female sex workers in South Africa. (21st June 2018) - Quaife, Matthew; Vickerman, Peter; Manian, Shanthi; Eakle, Robyn; Cabrera‐Escobar, Maria A.; Delany‐Moretlwe, Sinead; Terris‐Prestholt, Fern
Abstract: Evidence suggests that economic factors play an important role in commercial sex work, in particular that condomless sex commands a price premium relative to condom‐protected sex. This paper explores whether the use of a new HIV prevention product, with 100% efficacy but modeled after pre‐exposure prophylaxis (PrEP), could change the price and quantity of condomless commercial sex supplied. We collected stated preference data from 122 HIV‐negative female sex workers in urban South Africa, using a repeated choice experiment to simulate the impact of using PrEP on choices. Results suggest that the price premium for condomless sex would decrease by 73% with PrEP use and the quantity of condomless sex is predicted to increase by a factor of 2.27. Act price does not significantly affect choices without protection but strongly influences choices under full HIV protection. The utility offered by condoms reduces by around 15% under PrEP use. Because new HIV prevention products do not protect against other STIs or pregnancy, the unintended consequences of introducing HIV prevention products should be closely monitored, whereas users should not face stigma or blame for reacting rationally to exogenous changes to market conditions.